2022
DOI: 10.1016/j.jadohealth.2021.11.006
|View full text |Cite
|
Sign up to set email alerts
|

Using Substances to Cope With the COVID-19 Pandemic: U.S. National Data at Age 19 Years

Abstract: Purpose To examine predictors of using substances to cope with the COVID-19 pandemic, including pandemic-related isolation, stress, economic hardship, demographics, and prepandemic substance use. Methods A U.S. national sample (N = 1,244) was followed from the 12th grade in Spring 2019 to Fall 2020 (M = 19.6 years) when young adults were asked about their use of marijuana, vaping, drinking, and other drugs to cope. Results In Fall 2020, 15.7%… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
32
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 37 publications
(32 citation statements)
references
References 18 publications
0
32
0
Order By: Relevance
“…Additionally, while understanding the role of the COVID‐19 pandemic for these symptoms is important, it is perhaps more crucial to identify and implement effective coping strategies against pandemic‐related stressors. While some techniques, such as connecting socially with others (Waselewski et al, 2020 ) and maintaining a healthy diet, (Fullana et al, 2020 ) have been reported by young adults for improved mental wellbeing, other strategies, such as substance use to cope with pandemic‐related stress, are potentially damaging and can lead to future substance use problems (Patrick et al, 2021 ). Furthermore, less is known about the extent to which coping behaviors vary between those with pandemic‐related depressive and anxious symptoms and those with similar symptoms not attributed to the pandemic.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, while understanding the role of the COVID‐19 pandemic for these symptoms is important, it is perhaps more crucial to identify and implement effective coping strategies against pandemic‐related stressors. While some techniques, such as connecting socially with others (Waselewski et al, 2020 ) and maintaining a healthy diet, (Fullana et al, 2020 ) have been reported by young adults for improved mental wellbeing, other strategies, such as substance use to cope with pandemic‐related stress, are potentially damaging and can lead to future substance use problems (Patrick et al, 2021 ). Furthermore, less is known about the extent to which coping behaviors vary between those with pandemic‐related depressive and anxious symptoms and those with similar symptoms not attributed to the pandemic.…”
Section: Introductionmentioning
confidence: 99%
“…Somewhat consistent with previous research [ 15 , 35 ], we found significant increases in some reports of depressive symptoms, reductions in substance use, reductions in physical and sexual activity, and reductions in food insecurity ( Table 1 ). In concert with prior work examining changes in perceived norms and motivations for use [ 36 ]–particularly increases in using substances to cope [ 37 ]–it is clear that psychosocial risk factors for and prevalence of health behaviors have evolved across the pandemic. A critical contribution of the current study was the use of LCA to consider a broad set of indicators of health and well-being simultaneously, at each timepoint, and examine change over time.…”
Section: Discussionmentioning
confidence: 94%
“…Another notable sociodemographic factor associated with the increased usage of substances is isolation status, which was associated with a three-fold increased risk of increasing substance use during this COVID-19 pandemic period. There are significant data to support this association; a study involving US national data suggests a strong association between isolation during COVID-19 and prevalence or increase in substance use [ 36 ]. Isolation and solitary confinement during the pandemic also affected people who use drugs/alcohol, which then further changes their substance use pattern, specifically, increasing their usage [ 37 ].…”
Section: Discussionmentioning
confidence: 99%